The role of indicators in decisions of technology innovation - Boavida, Nuno F. F. G. (KIT Scientific Publishing, 2017)
There are thousands of indicators produced to understand and govern our societies. Studies about the way indicators are used in technological innovation are significantly rare, despite the centrality of these decisions to promote growth in our technology-intensive civilization. This book presents what is known and what was discovered in a doctoral research, which analysed innovative business leaders, policymakers and public researchers responsible for technological innovations.